2010
DOI: 10.1002/jcp.22178
|View full text |Cite
|
Sign up to set email alerts
|

Role of Annexin A1 in mouse myoblast cell differentiation

Abstract: Annexin A1 (ANXA1) is a calcium- and phospholipid-binding protein involved in a broad range of cellular events. This study used molecular and microscopy approaches to explore the role of ANXA1 in mouse myoblast C2C12 cell differentiation. We report that ANXA1 expression increases during differentiation and that the down-regulation of ANXA1 significantly inhibits the differentiation process. ANXA1 is expressed in vivo in both quiescent and activated satellite cells and is highly localized in the cells that migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 33 publications
6
57
1
Order By: Relevance
“…29 Cytosolic ANXA1 for example has been frequently implicated in cytoskeletal organization in several cellular models. 48,31,32,9,18,10 ANXA1 localization after hypoxia administration to PCa cell lines showed a noteworthy alteration of its expression profiles. The protein was indeed significantly expressed onto plasma membrane and in the extracellular environments over the time during hypoxia treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…29 Cytosolic ANXA1 for example has been frequently implicated in cytoskeletal organization in several cellular models. 48,31,32,9,18,10 ANXA1 localization after hypoxia administration to PCa cell lines showed a noteworthy alteration of its expression profiles. The protein was indeed significantly expressed onto plasma membrane and in the extracellular environments over the time during hypoxia treatment.…”
Section: Discussionmentioning
confidence: 95%
“…48 Proteins were visualized using the chemioluminescence detection system (Amersham) after incubation with primary antibodies against ANXA1 (rabbit polyclonal; 1:10000; 71-3400, Invitrogen), a-tubulin (mouse monoclonal; clone DM1A; 1:1000; Sigma-Aldrich), E-cadherin (mouse monoclonal; clone 36/E-Cadherin; 1:10000; BD Transduction Laboratories), vimentin (mouse monoclonal; clone E-5; 1:1000; Santa Cruz Biotechnologies), HIF1-a (rabbit polyclonal; clone A300-286A; 1:5000; Bethyl Laboratories), Ezrin (mouse monoclonal; clone 3C12; 1:250; Santa Cruz Biotechnologies), Moesin (mouse monoclonal; clone E-10; 1:250; Santa Cruz Biotechnologies), CK8 (mouse monoclonal, clone M20; 1:1000; Santa Cruz Biotechnologies), CK18 (mouse monoclonal, clone C-04; 1:1000; Santa Cruz Biotechnologies), p-ERK (rabbit monoclonal, clone Aw39; 1:1000; Cells Signaling), ERK (mouse monoclonal, clone MK12; Cells Signaling), p-p38 (mouse monoclonal; clone D-8; 1:1000; Santa Cruz Biotechnologies), p38 (rabbit polyclonal; clone C-20; 1:1000; Santa Cruz Biotechnologies), b-actin (mouse monoclonal; clone C-4, 1:1000; Santa Cruz Biotechnologies). The blots were exposed to Las4000 (GE Healthcare Life Sciences) and the relative band intensities were determined using ImageQuant software (GE Healthcare Life Sciences).…”
Section: Western Blottingmentioning
confidence: 99%
“…ANXA1 is a calcium-and phospholipid-binding protein involved in regulating a broad range of cellular events, including migration in different types of cells such as myoblasts, leukemia, and breast cancer lines and endothelial cells (7,26,47,48). Moreover, a recent study showed that ANXA1 ÏȘ/ÏȘ mice are unable to heal the damage associated with indomethacin-induced gastric ulcers (30).…”
Section: Discussionmentioning
confidence: 99%
“…These candidates are relevant to other associated diseases, the apoptotic pathway and synthetic substances in tissues (24)(25)(26). However, the development of these in the process of IgAN are completely undetermined, and therefore, these novel candidates require further investigation.…”
Section: Discussionmentioning
confidence: 99%